Pengontrolan Debit Air Melalui Ethernet Di Tangki Kembar Dengan Metode Proporsional Integratif Menggunakan Arduino - Adnanqays Graha Riyadhi; Erwin Susanto; Ig Prasetya Dwi Wibawa (eProceedings of Engineering, 2016)
This paper proposes proportional integrative control method for twin tank’s debit control by Ethernet using arduino. An ultrasonic sensor was mounted in top of twin tanks to measure a height that can be converted into debit with some calculation. An Ethernet modul was used for communication between PC and twin tank. Bigger the debit will make time rise increase because water must fill the tank first. Keywords: Arduino; Debit control; Integrative; Proportional